Chinamitales: defensores y justicias k’ichee’ en las comunidades indígenas del altiplano de Guatemala colonial - Jones, Owen H. (2016)
The present article examines the functions of indigenous advocates whose position as ward leaders (chinamitales) in K’ichee’ societies existed in Pre-Columbian Mesoamerica and continued into the colonial nineteenth century in Guatemala. This was a hereditary legal and administrative position that elites in K’ichee’an society enjoyed as a result and reward of military conquest in the Pre-Columbian era. Chinamitales advocated for the inhabitants of their wards who were both elites and non-elites in land disputes and in criminal matters. They persisted in indigenous communities from the sixteenth century to the nineteenth century as officially unrecognized legal advocates who participated in tribunals in indigenous communities at the local level and advocated for their constituents before their indigenous town councils. They also acted in a similar capacity as the indigenous municipal council, making last testaments, nominating candidates for local town council elections and positions in the church laity, collecting tribute, and choosing laborers for the repartimiento. Their advocacy spilled over into colonial judicial proceedings at the regional and high court levels when disagreements arose within indigenous communities over land disenfranchisement and whenever they sensed that the indigenous municipal council was not protecting their interests.